EFEKTIVITAS KOMUNIKASI NEGOSIASI DALAM BISNIS - Dwi Utami, Faiqotul Isma (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2017)
The need for communication in today’s business competition is constantly changing. The process of negotiation becomes an important thing in supporting the progress of a business. Negotiations are used to bridge different interests, between producers and consumers. A negotiator must be able to persuade the other person so that they can follow the negotiator’s will without them knowing it. This paper explains how a business can communicate more effectively so that he can become a good negotiator.